Serial [18F]-fluoromisonidazole PET during radiochemotherapy for locally advanced head and neck cancer and its correlation with outcome. Issue 1 (October 2015) - Wiedenmann, Nicole E.; Bucher, Sabine; Hentschel, Michael; Mix, Michael; Vach, Werner; Bittner, Martin-Immanuel; Nestle, Ursula; Pfeiffer, Jens; Weber, Wolfgang A.; Grosu, Anca L.
Abstract: Purpose: The aim was to assess changes of tumour hypoxia during primary radiochemotherapy (RCT) for head and neck cancer (HNC) and to evaluate their relationship with treatment outcome. Material and methods: Hypoxia was assessed by FMISO-PET in weeks 0, 2 and 5 of RCT. The tumour volume (TV) was determined using FDG-PET/MRI/CT co-registered images. The level of hypoxia was quantified on FMISO-PET as TBRmax (SUVmaxTV/SUVmean background). The hypoxic subvolume (HSV) was defined as TV that showed FMISO uptake ⩾1.4 times blood pool activity. Results: Sixteen consecutive patients (T3–4, N+, M0) were included (mean follow-up 31, median 44 months). Mean TBRmax decreased significantly ( p < 0.05) from 1.94 to 1.57 (week 2) and 1.27 (week 5). Mean HSV in week 2 and week 5 (HSV2 = 5.8 ml, HSV3 = 0.3 ml) were significantly ( p < 0.05) smaller than at baseline (HSV1 = 15.8 ml). Kaplan–Meier plots of local recurrence free survival stratified at the median TBRmax showed superior local control for less hypoxic tumours, the difference being significant at baseline and after 2 weeks ( p = 0.031, p = 0.016). Conclusions: FMISO-PET documented that in most HNC reoxygenation starts early during RCT and is correlated with better outcome.